2010
DOI: 10.1126/science.1183765
|View full text |Cite
|
Sign up to set email alerts
|

Doc2b Is a High-Affinity Ca 2+ Sensor for Spontaneous Neurotransmitter Release

Abstract: Synaptic vesicle fusion in brain synapses occurs in phases that are either tightly coupled to action potentials (synchronous), immediately following action potentials (asynchronous) or as stochastic events in the absence of action potentials (spontaneous). Synaptotagmin-1, -2 and -9 are vesicleassociated Ca 2+ -sensors for synchronous release. Here we found that Double C2 domain (Doc2) proteins act as Ca 2+ -sensors to trigger spontaneous release. Although Doc2 proteins are cytosolic, they function analogously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
396
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(435 citation statements)
references
References 45 publications
(83 reference statements)
36
396
3
Order By: Relevance
“…S2C), making difficult to predict whether these domains might adopt the closed or open conformation without further experimentation. However, it is clear that the similarity of DOC2B to rabphilin 3A is higher than to syt1, and this might explain the different behaviors found for it in recent studies using KO mice (38)(39)(40).…”
Section: Resultsmentioning
confidence: 67%
“…S2C), making difficult to predict whether these domains might adopt the closed or open conformation without further experimentation. However, it is clear that the similarity of DOC2B to rabphilin 3A is higher than to syt1, and this might explain the different behaviors found for it in recent studies using KO mice (38)(39)(40).…”
Section: Resultsmentioning
confidence: 67%
“…Previous studies showed that multiple Ca 2+ sensors control spontaneous release, including Syt1 (15) and Doc2s (16,17). We therefore hypothesized that in the absence of Syt1 phosphorylation, Doc2s mediate the increased spontaneous release.…”
Section: Phosphorylation Of T112 Is Essential For Phorbol Ester-inducedmentioning
confidence: 99%
“…Syt1 is the vesicular Ca 2+ sensor that mediates fast AP-evoked release in the hippocampus (14) and drives a large fraction of spontaneous release (15). In the latter case, Syt1 competes with alternative sensors, in particular Doc2s, for SNARE binding and the initiation of vesicle fusion (16,17). Syt1 bears a highly conserved phosphorylation site (threonine 112) in a putative α-helix in the linker between the transmembrane (TM) and C2A domain that can be phosphorylated by PKC and Ca 2+ /calmodulin (CaM)-dependent protein kinase II (CaMK-II, refs.…”
mentioning
confidence: 99%
“…forms of release involve different Ca 2+ sensors (39). Compared with other members of the family, BoTx D has a greater effect on spontaneous release.…”
Section: Presynaptic Manipulations That Reduce Spontaneous Transmittermentioning
confidence: 99%